2016
DOI: 10.1097/jom.0000000000000883
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and Ocular Symptoms Among Employees at Swedish Indoor Swimming Pools

Abstract: The findings indicate that indoor swimming pool environments may have irritating effects on mucous membranes. FeNO data also indicate an inflammatory effect on central airways, but the clinical relevance is unclear. Low trichloramine levels found in this study were not associated with health effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
2
9
2
Order By: Relevance
“…However, personal trichloramine concentrations over the median concentration (20 mg/m 3 ) were found to be associated with a statistically significant increased risk of developing at least one ocular symptom during the last week when adjusting for confounding factors. These findings are in accordance with that of Lofstedt et al, [19] who reported an increased risk of ocular, nasal, and respiratory symptoms occurring during the last week among exposed swimming pool workers. Also, Parrat et al [21] found that the occurrence of eye and nose irritation was connected with trichloramine exposure.…”
Section: Dose-response Relationshipsupporting
confidence: 93%
See 4 more Smart Citations
“…However, personal trichloramine concentrations over the median concentration (20 mg/m 3 ) were found to be associated with a statistically significant increased risk of developing at least one ocular symptom during the last week when adjusting for confounding factors. These findings are in accordance with that of Lofstedt et al, [19] who reported an increased risk of ocular, nasal, and respiratory symptoms occurring during the last week among exposed swimming pool workers. Also, Parrat et al [21] found that the occurrence of eye and nose irritation was connected with trichloramine exposure.…”
Section: Dose-response Relationshipsupporting
confidence: 93%
“…Similar findings were reported for public swimming pool employees. [19] These findings concurred with those of a previous study [40] that reported mild eosinophilic airway inflammation for highly trained swimmers. Indistinguishable FE NO levels have also been reported for swimming pool environments.…”
Section: Lung Function Fe No and Pefsupporting
confidence: 91%
See 3 more Smart Citations